2019
DOI: 10.1177/1120672119862878
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary glaucoma and visual axis opacification in aphakic and pseudophakic patients following congenital cataract surgery: A 28-year longitudinal case series

Abstract: Purpose: To determine the incidence, timing and risk factors for glaucoma and visual axis opacification development following surgery for congenital cataract in the first year of life. Methods: A prospective case series of all cataract surgery performed in Temple Street Children’s University Hospital over a 28-year period was conducted. A total of 93 subjects (135 eyes) were analysed. Sixty-two eyes had a primary intraocular lens inserted at the time of surgery; 73 eyes were aphakic. We recorded patient demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…Studies demonstrated that average duration of surgery was 2.5 years. 12,13 In the present study we found that the frequency of pseudophakic glaucoma was 32 (33.68%) while 63 (66.32%) patients had no glaucoma finding. Patients who received ECCE had high rate of glaucoma 28 (45.16%) as compared to phacoemulsification in 4 (12.12%) patients.…”
Section: Discussionsupporting
confidence: 49%
“…Studies demonstrated that average duration of surgery was 2.5 years. 12,13 In the present study we found that the frequency of pseudophakic glaucoma was 32 (33.68%) while 63 (66.32%) patients had no glaucoma finding. Patients who received ECCE had high rate of glaucoma 28 (45.16%) as compared to phacoemulsification in 4 (12.12%) patients.…”
Section: Discussionsupporting
confidence: 49%
“…Of these potentially relevant articles, 176 publications were excluded for various reasons, and 33 publications met the inclusion criteria and were included in this report. These comprised 3 RCTs [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 15 nonrandomized studies, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] relevant to research questions 1, 2, 3, and 4. No economic evaluations relevant to research questions 5 and 6 were identified. There were 16 clinical publications and 1 methods publication (which was not included in the overall count) 77 that reported on the same RCT -the Infant Aphakia Treatment Study (IATS).…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…The RCTs were conducted in the US [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]77 and India. 60,61 The nonrandomized studies were conducted in the US, [63][64][65] Germany, 66 Ireland, 67,68 UK, 69 Latvia, 70 China, 71 India, [72][73][74] France, 75 Brazil, 62 and Korea. 76 There were multiple publications for the IATS, which were published in 2020, 46,50,53 2016, 55,56 2015, 52,59 2014, 45,49,58 2013, 54,57 2012, 51 2011, 47,48 and 2010.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations